Retrospective evaluation of canine and feline maxillomandibular trauma cases - Mulherin, B. L.; Snyder, C. J.; Soukup, J. W.; Hetzel, S. (Veterinary and Comparative Orthopaedics and Traumatology, 2014)
Objectives: To determine relationships between seasonality and lunar cycle and the frequency of maxillomandibular (MM) and non-maxillomandibular (non-MM) injury in canine and feline trauma patients.Methods: A medical records database was searched to identify all MM trauma patients (n = 67) and a random sample of non-MM trauma patients (n = 129) according to search criteria. Season of injury, moon phase, and moon luminosity were calculated for the date of injury.Results: Maxillomandibular injury occurred predominately in the spring and decreased through winter while non-MM injury occurred more frequently in the summer and fall. The difference in the frequency of MM and non-MM injuries during different seasons was not significant (p = 0.071). When comparing the amount of moon illuminated when injuries occurred during the quarters before or after the full moon, a difference (p = 0.007) was noted with a greater number of injuries occurring immediately following the full moon.Clinical significance: These results may guide clinicians to closely evaluate trauma patients that are presented on emergency during a particular season or lunar phase. Based on the season at the time of injury, close evaluation for MM versus non-MM trauma may be appropriate.
Keywords: Maxillomandibular; trauma; fracture; lunar cycle; seasonality; injury